'I don't necessarily identify myself as a Muslim [RE] teacher?': considering the limitations of the category 'Muslim' in the case of 'Muslim RE teachers'. Issue 1 (2nd January 2021) - Vince, Matthew
ABSTRACT: Given the current context of Prevent and Fundamental British Values, there has been a surge in academic and political interest surrounding Muslim identities in British educational contexts. Noting this 'religious turn' in educational debate, scholars have begun to question the mobilisation of 'Muslim' and 'Muslimness', suggesting that there are limits to such identification. This paper considers their critique through an exploration of how 'Muslim RE teachers' understood and experienced their personal and professional identities, based on recent qualitative research conducted with 21 'Muslim RE teachers' across England. Findings reveal that notions of being a 'Muslim RE teacher' are heavily contested, and instead highlight a fluid and dynamic spectrum of configurations of the participants' 'Muslim' and 'RE teacher' identities. The paper argues in support of the above critique, demonstrating that the assumed primacy of their 'Muslimness' limits the multiplicity of these participants' identities, and so does not reflect their empirical understanding and experience. The paper then suggests a move towards a more sophisticated understanding of identity, encapsulated in the notion of the 'RE teacher who is Muslim'.